Statement of the most important knowledge in Arabic grammar - Dr. Ibrahim Khalaf Saleh Al-Qaisi (Journal of College of Education, 2026)
I began my research on this topic in books on language, grammar, morphology, dictionaries, exegesis, and Quranic sciences, as they contain everything related to the Arabic language regarding the types of definite articles. A group of scholars addressed this topic as "the most well-known definite article," and they agreed that the Divine Name (Allah) is the most well-known definite article. They differed on the definite articles that follow it.In this research, I concluded that the Divine Name (Allah) is the most well-known definite article, according to ancient and modern grammarians. Grammarians differed on the other types of definite articles, with some arguing that they are all equal, since definite articles are not differentiated.
Keywords: statement, knowledge, grammar, the name of God